2015
DOI: 10.1159/000434720
|View full text |Cite
|
Sign up to set email alerts
|

Future Directions in the Study of Personality in Adulthood and Older Age

Abstract: Over the past 20 years, empirical evidence has brought about a change in the view on how, or even whether, personality traits change or develop in adulthood and later life. Now we know personality can and does change for many people, if not most. Changes in personality may occur due to biological or environmental factors. This paper presents key empirical findings on personality change in adulthood and provides evidence that personality change affects mental and physical health. Our goal is to provide a broad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 53 publications
1
13
0
1
Order By: Relevance
“…It has the potential to influence health via several mechanisms [10], including engagement in health-damaging or health-enhancing behaviours, illness behaviour in response to symptom perception or diagnosis of illness, or susceptibility to stress-induced physiological arousal, which may contribute to the development or progression of illness. There is evidence that levels of personality traits may change in adulthood in some people, if not in most, possibly in response to biological or environmental factors [1113]. Such changes have been linked with later adverse health outcomes, including mortality [14].…”
Section: Introductionmentioning
confidence: 99%
“…It has the potential to influence health via several mechanisms [10], including engagement in health-damaging or health-enhancing behaviours, illness behaviour in response to symptom perception or diagnosis of illness, or susceptibility to stress-induced physiological arousal, which may contribute to the development or progression of illness. There is evidence that levels of personality traits may change in adulthood in some people, if not in most, possibly in response to biological or environmental factors [1113]. Such changes have been linked with later adverse health outcomes, including mortality [14].…”
Section: Introductionmentioning
confidence: 99%
“…Future work should consider whether SRM changes when an individual finds out their relative has dementia. Similarly, some studies have identified personality changes with age 48 that may impact older adults' SRM over time as well. Despite these limitations, this study has several strengths.…”
Section: Discussionmentioning
confidence: 99%
“…Kepribadian sebagai aspek non biologis memiliki fungsi utama dalam menentukan aksi dan perilaku untuk menghadapi/mencari solusi melalui fungsi kognitif dan fungsi emosinya (Shaw, Nguyen, Satterfield, Ramirez, & McKnight, 2015;Hill dkk, 2014). Selain itu kepribadian dalam beberapa penelitian ternyata dapat mengalami perubahan (permeable) bagi mayoritas orang (Jones & Meredith, 1996;Bleidorn, Kandler, Riemann, Spinath, & Angleitner, 2009;Leszko, Elleman, Bastarache, Graham, & Mroczek, 2016). Dalam segi pendidikan (Alkies & Temizel, 2018;Erton, 2010), kepribadian juga ditemukan memiliki pengaruh terhadap tipe media pembelajaran termasuk juga dalam bahasa, begitu juga jika seorang individu memiliki cita-cita menjadi seorang atlet atau pekerja lapangan berarti harus memiliki dominasi kepribadian extrovert supaya unggul (Akpinar & Akpinar, 2018).…”
Section: Pendahuluanunclassified